2018
DOI: 10.1111/ijfs.13781
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of apple (Malus domestica Borkh) polyphenol oxidases by radio frequency combined with pulsed electric field treatment

Abstract: Summary Radio frequency (RF) preprocessing combined with pulsed electric field (PEF) processing was employed to inactivate polyphenol oxidase (PPO) in apple juice. PPO enzyme levels, loss of total phenolic content (TPC), colours and volatile components in the apple juice were subsequently determined and compared with conventional processing methods (60 °C for 10 min and 70 °C for 10 min). Results indicated that, when the apple tissue was preprocessed using RF for 10 min, the residual activity of PPO decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…This method also minimise the nutritional loses by inactivating the microorganisms and enzymes in a short time compared to other traditional thermal processes (Siguemoto et al ., ). The combination of different novel techniques has been confirmed that they were able to control the microbial load, enzymatic activities and enhance the food safety of juices (Aadil et al ., , ; Chang et al ., ; Tian et al ., ). Therefore, the combination of these two techniques is useful to improve the safety and quality of SCJ, which is the objective of this study.…”
Section: Introductionmentioning
confidence: 97%
“…This method also minimise the nutritional loses by inactivating the microorganisms and enzymes in a short time compared to other traditional thermal processes (Siguemoto et al ., ). The combination of different novel techniques has been confirmed that they were able to control the microbial load, enzymatic activities and enhance the food safety of juices (Aadil et al ., , ; Chang et al ., ; Tian et al ., ). Therefore, the combination of these two techniques is useful to improve the safety and quality of SCJ, which is the objective of this study.…”
Section: Introductionmentioning
confidence: 97%
“…So, there is a need for the preservation and availability of safe, fresh and healthy spinach juice through some novel processing techniques (Zhang et al., 2019). A combination of PEF and US have synergetic effect in higher inhibition of microbial and enzymatic activity and enhancement of nutrition and product quality of juices (Aadil et al., 2015; Siddeeg et al., 2019b; Tian et al., 2018). Furthermore, these techniques are being used together due to their simplicity, economy, efficiency, and constancy for reducing the activity of microorganisms, which prove the better way to treat fruit juice (Li et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed electric fields (PEF), regarded as an emerging non‐thermal treatment technology, has been used in inactivation of pathogenic microorganisms in food processing, which can also improve the colour, texture and flavour (Lee et al ., ; Fauster et al ., ; Tian et al ., ) of food compared with other thermal processing approaches (Gonzalez‐Casado et al ., ). Besides, PEF techniques have been employed to modify the structures of the polymer compounds such as starch (Hong et al ., , ) and ovalbumin nanotube (Wei et al ., ).…”
Section: Introductionmentioning
confidence: 99%